In-situ fabrication of Ce-doped CuAl-LDH@Ce composite superhydrophobic coating on 2219 aluminum alloy: Self-healing anti-corrosion performance and mechanism investigation - Yuheng Sun; Jiaxin Lu; Dongyu Huang; Hao Yang; Hongqun Tang; Qiaoning Chen; Guangming Zhang; Youbin Wang; Yabin Zhang (Journal of Materials Research and Technology)
2219 aluminum alloy is widely used in shipbuilding for its high strength and light weight, but its high Cu content causes severe localized corrosion in marine environments, shortening service life. This study proposes a novel “in-situ growth--Ce3+-doping--superhydrophobic modification” strategy. A self-healing CuAl-LDH@Ce composite coating was prepared via one-step hydrothermal in-situ growth, followed by silane-mediated superhydrophobic modification. Electrochemical tests show the coating enhances barrier effect with |Z|0.01Hz at 1.36 × 106 Ω cm2. Ce3+-doping enables self-healing via CeO2 deposition, reducing corrosion current density to 2.69 × 10−3 μA cm−2 (four orders of magnitude lower than the substrate), while the superhydrophobic surface (contact angle 162.8°) synergistically suppresses medium penetration. The mechanism reveals that coating achieves dynamic corrosion protection through LDH anion exchange, scratch self-healing via CeO2 deposition, and anti-adhesion via superhydrophobic interface, establishing a multifunctional protection paradigm. This study develops a hierarchically integrated protection network comprising “physical barrier, chemical passivation, and interface regulation,” which goes beyond traditional single-mechanism protection and enhances the corrosion resistance and self-healing performance of 2219 aluminum alloy. It provides fundamental corrosion inhibition insights and scalable solutions for high-performance Al alloys in harsh environments.